Digital Defense Drives Economic Growth in Indonesia and Uzbekistan - Budiono, Arief; Alba, Gradia Okultra; Gulyamov, Said Saidakhrarovich; Ali Polatjon Ogli , Turdialiev Mukhammad (Lembaga Contrarius Indonesia, 2025)
Digital technologies drive economic growth in both Indonesia and Uzbekistan. The global economy increasingly depends on the digital economy, reflected in the rise of blockchain systems, digital banking, and other digital activities in the economic sector. This research highlights the importance of digital personal data protection in Uzbekistan and Indonesia and examines its connection to digital economic development in both countries. The study uses a normative legal method that combines statutory and conceptual approaches. The authors examine the relevant laws and explore the concept of personal data protection in each country. The findings present two main points. First, the laws in both countries regulate personal data protection and assign institutional responsibilities across administrative, civil, and criminal domains. Second, when conflicts, data breaches, or criminal actions involving personal data occur, the legal systems provide for resolution through court litigation. Although both countries have implemented personal data protection laws that support digital economic development, they differ in institutional structure, legal procedures, and the scope of authority. Weak personal data protection may hinder the growth of the digital economy in both nations.